Centro de salud tipo A. El Batán - Constante Ochoa, Diana Pamela (2020)
In the Urban Plan carried out at the AR0860 workshop in the El Batán neighborhood focused on a university citadel, generating a proposal with housing and facilities of interest to people to live in the sector, in relation to the problems encountered in the area of study, It was possible to diagnose that in the neighbourhood, although there were several health-care centres nearby, there was no public care for the sector. The proposal for a Type A Health Centre is therefore adequate to meet the needs of public health rights and to respond to these and future needs.